Incremental prognostic value of worsening renal function parameters in addition to the GRACE score in patients with acute coronary syndrome. (14th October 2021) - Presume, J; Gomes, D; Albuquerque, F; Strong, C; Trabulo, M; De Araujo Goncalves, P; Campante Teles, R; Almeida, M; Mendes, M; Ferreira, J
Abstract: Background: Baseline renal function, one of the parameters included in the GRACE score, has prognostic relevance in patients admitted for acute coronary syndrome (ACS). Purpose: The aim of this study was to compare different worsening renal function (WRF) parameters during hospitalization for ACS and their impact on all-cause mortality. Furthermore, we aimed to assess if these parameters had any incremental prognostic value in addition to the GRACE score. Methods: We conducted a single-center retrospective study enrolling consecutive patients admitted for ACS from January 2016 to December 2018. Estimation of glomerular filtration rate (eGFR) for each patient was calculated based on the CKD-EPI formula. WRF during hospitalization was assessed by means of: serum creatinine (sCr) elevation ≥0, 3mg/dL, duplication of the sCr value or maximum sCr value ≥2, 0mg/dL. Results: A total of 555 patients were included (65±13 years old, 72% male). Overall, 402 (72%) had hypertension, 167 (30%) were diabetic, 88 (16%) had left ventricular ejection fraction <40%. Mean GRACE score was 102.7±29.1 and median sCr at baseline was 0.83 mg/dL [0.70; 0.97]. Median length of hospitalization was 4 days [2; 10] and the mean follow-up of 963 days. Baseline eGFR showed significant correlation with mortality during follow-up (HR 0.742 [95% CI 0.691–0.797] per 10 mL/min/1.73m 2 increase in eGRF). Moreover, all WRF parameters showed significant association with all-cause mortality during follow-up on a univariate analysis - p<0, 001 (Table 1). Elevation of sCr ≥0, 3 mg/dL during hospitalization was the most frequent WRF parameter (210 patients - 38%) and the most sensitive parameter to predict our endpoint, occurring in 56 patients who died during follow-up (sensitivity 66.7%). Both duplication of sCr and absolute sCr ≥2, 0mg/dL during hospitalization showed a lower prevalence; however, the majority of patients with one of these findings died during follow-up (51, 4% and 68, 5%, respectively). On a multivariate Cox regression analysis, adjusted for the GRACE score, all individual WRF parameters remained independently associated with all-cause mortality during follow up (Table 2). Conclusion: Worsening renal function has significant prognostic impact in patients admitted for ACS. Identification of these parameters during hospitalization adds significant value to the prognostic stratification of the GRACE score. Funding Acknowledgement: Type of funding sources: None.